Anti-oxidation negative plate lead paste, negative plate lead paste preparation process and negative plate

By using antioxidant negative electrode lead paste in lead-acid batteries, combined with composite porous carbon, cage-shaped materials and other components, the problems of insufficient service life and charging efficiency of existing lead-acid batteries are solved, and higher battery life and lower capacity attenuation are achieved.

CN115275172BActive Publication Date: 2025-05-09TIANNENG GRP HENAN ENERGY TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211076433.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-05
Publication Date
2025-05-09
Estimated Expiration
2042-09-05

AI Technical Summary

Technical Problem

There is room for improvement in the service life and charging efficiency of existing lead-acid batteries, especially in terms of antioxidant performance and plate material utilization.

Method used

An antioxidant negative electrode lead paste is used, including sulfonated oak powder, composite porous carbon, cage material, composite material, short fiber, conductive carbon black and sulfuric acid solution, and the antioxidant performance of lead paste is improved through a specific preparation process.

Benefits of technology

It significantly improves the service life and charging efficiency of lead-acid batteries, reduces water consumption, and reduces early capacity loss of plate materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003831359390000131
    Figure BDA0003831359390000131
Patent Text Reader

Abstract

The invention relates to the technical field of lead-acid battery production, in particular to an antioxidant negative plate lead paste, a negative plate lead paste preparation process and a negative plate. The antioxidant negative plate lead paste comprises the following components: sulfonated oak powder, composite porous carbon, cage-type material, composite material, short fiber, conductive carbon black, sulfuric acid solution with a mass percentage concentration of 50%, deionized water, and lead powder. The composite porous carbon enables the plate to have a higher specific surface area, and the solid solution of bismuth oxide and cobalt oxide contained therein has an electrocatalytic effect, promotes the recombination of hydrogen and oxygen, and the regeneration of the active material of the negative plate, and inhibits the precipitation of hydrogen to a certain extent. The cage-type material inhibits the continuous growth of lead sulfate crystals and reduces the water loss of the electrolyte. The lead-acid battery obtained by making the antioxidant negative plate lead paste into an antioxidant negative plate has a higher cycle life and a significantly reduced capacity decay rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lead-acid battery production, in particular to an anti-oxidation negative electrode plate lead paste, a preparation process of the negative electrode plate lead paste and a negative electrode plate. Background Art

[0002] The active materials of lead-acid batteries are closely related to the performance of lead-acid batteries, affecting or even determining the specific power, specific energy, large current discharge capacity, charging efficiency, cycle life, etc. of lead-acid batteries. The preparation and application of current active materials for lead-acid batteries have enabled lead-acid batteries to achieve relatively practical and good performance. Generally, by adding some common conductive agents, dispersants, expanders, etc. to the active materials, a utilization rate of 30%-60% of the positive and negative active materials and a good charging efficiency can be obtained, and the problems of sulfation, softening and shedding of positive active materials, and early capacity loss can be more or less controlled or alleviated, but there is still considerable room for improvement and problems.

[0003] The performance and quality of the battery are greatly affected by the formula of the negative plate lead paste. How to make a suitable lead paste is related to the comprehensive performance of the lead-acid battery. Summary of the invention

[0004] Based on the above technical problems, the present invention provides an antioxidant negative plate lead paste and a preparation process for improving the service life of lead-acid batteries. The present invention also provides an antioxidant negative plate obtained by using the above antioxidant negative plate lead paste preparation process.

[0005] The present invention provides an antioxidant negative plate lead paste, comprising the following components in parts by weight: 0.5-2 parts of sulfonated oak powder, 3-10 parts of composite porous carbon, 5-7 parts of cage-type materials, 0.5-2 parts of composite materials, 0.1-0.5 parts of short fibers, 1-3 parts of conductive carbon black, 8-15 parts of sulfuric acid solution with a mass percentage concentration of 50%, 9-18 parts of deionized water, and 80-100 parts of lead powder;

[0006] The composite porous carbon preparation method is as follows:

[0007] Step 1: adding bismuth nitrate and cobalt nitrate into an ethanol aqueous solution to form a 100 ml metal solution, wherein the ethanol aqueous solution is an ethanol aqueous solution with a mass fraction of 50%, the concentration of bismuth ions in the metal solution is 50 mmol / L, and the concentration of cobalt ions in the metal solution is 50 mmol / L;

[0008] Step 2: Add the metal solution in step 1 to the reaction kettle, then add 10 mmol of 3,5-dicarboxyphenylboronic acid and 10 mmol of terephthalic acid, react at 100-200° C. for 24 hours, wash the product with ethanol three times, and dry it at 50-70° C. in vacuum to obtain a crystalline product;

[0009] Step 3: calcining the crystalline product in step 2 at 600° C. for 9 h in a nitrogen atmosphere to obtain a composite porous carbon;

[0010] The cage material is formed by molecular self-assembly of tetrapyridylporphyrin cobalt, cis-Pt(PEt3)2(OTf)2 and [1,1'-biphenyl]-3,3',5,5'-sodium tetracarboxylate.

[0011] Specifically, the composite material is prepared by mixing and grinding sodium lignin sulfonate, lignin and barium sulfate in a weight ratio of 3:2:3.

[0012] Specifically, the short fiber is one of nylon, acrylic and polyester, and has a length of 2-4 mm.

[0013] Specifically, the method for preparing the cage material is as follows:

[0014] Step 1: Add 0.1 mol of tetrapyridylporphyrin cobalt and 0.4 mol of cis-Pt(PEt3)2(OTf)2 into 400 ml of acetone and heat to 50 °C for 12 h;

[0015] Step 2: Dissolve 0.1 mol of sodium [1,1'-biphenyl]-3,3',5,5'-tetracarboxylate in 100 ml of deionized water, add to the mixture in step 1, and heat to 50°C for 12 hours;

[0016] Step 3: Cool to room temperature, remove the solvent under nitrogen protection, and disperse the product in 100 ml of acetone. After dialyzing, add 300 ml of ether to produce precipitation, filter and dry to obtain a cage-type material.

[0017] The present invention also provides a process for preparing an antioxidant negative plate lead paste, comprising the following steps:

[0018] (a) weighing the above raw materials according to the above weight fractions, mechanically premixing the composite material and the conductive carbon black, adding the sulfonated oak powder, the composite porous carbon, the cage material and the short fiber after the premixing is uniform, and then mechanically mixing them, and after the premixing is uniform, dispersing the whole in the lead powder and dry stirring to obtain a mixture;

[0019] (b) adding deionized water to the mixture of step 1 and stirring evenly, then slowly adding sulfuric acid solution, controlling the system temperature between 30-65° C. during the acid addition process, and continuously stirring for 20-30 minutes throughout the process to prepare the antioxidant negative electrode lead paste.

[0020] The present invention also provides an antioxidant negative electrode plate, which is made by the following steps: the antioxidant negative electrode plate lead paste obtained by the above-mentioned preparation process is applied to the negative electrode grid, and dried and solidified; during drying and solidification, the curing time is 30 hours, the temperature is 50°C, and the relative humidity is 95%; the drying time is 32 hours, and the temperature is 55°C.

[0021] Beneficial effects:

[0022] The composite porous carbon contains a solid solution of bismuth oxide and cobalt oxide and is doped with boron, so that the antioxidant negative plate has a higher specific surface area. The solid solution of bismuth oxide and cobalt oxide has an electrocatalytic effect that can promote the reduction of oxygen and lead sulfate, promote the recombination of hydrogen and oxygen, and regenerate the active substances of the antioxidant negative plate, thereby reducing water consumption and increasing the service life of the battery. The intervention of boron significantly improves the oxygen adsorption and activation capacity and increases the recombination capacity of hydrogen and oxygen. Finally, the solid solution of bismuth oxide and cobalt oxide also has the effect of inhibiting the precipitation of hydrogen to a certain extent.

[0023] The cage material can inhibit the continuous growth of lead sulfate crystals, fragment the generated lead sulfate, and make it difficult to form a whole. Therefore, the lead sulfate is easily reduced and converted into lead dioxide, which increases the service life of the battery. In addition, the cobalt complex in the cage material can promote the reduction of oxygen, increase the recombination rate of oxygen and hydrogen, and reduce the loss of water in the electrode liquid. DETAILED DESCRIPTION

[0024] Example 1

[0025] An antioxidant negative plate lead paste, comprising the following components in parts by weight: 0.5 parts of sulfonated oak powder, 3 parts of composite porous carbon, 5 parts of cage-type material, 0.5 parts of composite material, 0.1 parts of short fibers, 1 part of conductive carbon black, 8 parts of sulfuric acid solution with a mass percentage concentration of 50%, 9 parts of deionized water, and 80 parts of lead powder;

[0026] The composite porous carbon preparation method is as follows:

[0027] Step 1: adding bismuth nitrate and cobalt nitrate into an ethanol aqueous solution to form a 100 ml metal solution, wherein the ethanol aqueous solution is an ethanol aqueous solution with a mass fraction of 50%, the concentration of bismuth ions in the metal solution is 50 mmol / L, and the concentration of cobalt ions in the metal solution is 50 mmol / L;

[0028] Step 2: Add the metal solution in step 1 to the reaction kettle, then add 10 mmol of 3,5-dicarboxyphenylboronic acid and 10 mmol of terephthalic acid, react at 100°C for 24 hours, wash the product with ethanol three times, and dry it at 50°C in vacuum to obtain a crystalline product;

[0029] Step 3: calcine the crystalline product in step 2 at 600°C for 9 hours in a nitrogen atmosphere to obtain composite porous carbon.

[0030] The cage material is prepared by molecular self-assembly of tetrapyridylporphyrin cobalt, cis-Pt(PEt3)2(OTf)2 and [1,1'-biphenyl]-3,3',5,5'-tetracarboxylate sodium, and the specific preparation method is as follows:

[0031] Step 1: Add 0.1 mol of tetrapyridylporphyrin cobalt and 0.4 mol of cis-Pt(PEt3)2(OTf)2 into 400 ml of acetone and heat to 50 °C for 12 h;

[0032] Step 2: Dissolve 0.1 mol of sodium [1,1'-biphenyl]-3,3',5,5'-tetracarboxylate in 100 ml of deionized water, add to the mixture in step 1, and heat to 50°C for 12 hours;

[0033] Step 3: Cool to room temperature, remove the solvent under nitrogen protection, and disperse the product in 100 ml of acetone. After dialyzing, add 300 ml of ether to produce precipitation, filter and dry to obtain a cage-type material.

[0034] The composite material is prepared by mixing and grinding sodium lignin sulfonate, lignin and barium sulfate in a weight ratio of 3:2:3.

[0035] The short fibers are nylon and have a length of 2 mm.

[0036] A preparation process of an anti-oxidation negative plate lead paste, characterized in that it comprises the following steps:

[0037] (a) weighing the above raw materials according to the above weight fractions, mechanically premixing the composite material and the conductive carbon black, adding the sulfonated oak powder, the composite porous carbon, the cage material and the short fiber after the premixing is uniform, and then mechanically mixing them, and after the premixing is uniform, dispersing the whole in the lead powder and dry stirring to obtain a mixture;

[0038] (b) adding deionized water to the mixture of step 1 and stirring evenly, then slowly adding sulfuric acid solution, the system temperature is controlled at 30° C. during the acid addition process, and stirring is continued for 20 minutes throughout the process to prepare the antioxidant negative electrode lead paste.

[0039] An anti-oxidation negative electrode plate, the anti-oxidation negative electrode plate lead paste obtained by the above-mentioned preparation process is made by the following steps:

[0040] The anti-oxidation negative plate lead paste is applied to the negative grid plate and dried and cured; during drying and curing, the curing time is 30 hours, the temperature is 50° C., and the relative humidity is 95%; the drying time is 32 hours, and the temperature is 55° C.

[0041] Example 2

[0042] An anti-oxidation negative plate lead paste, comprising the following components in parts by weight: 1.2 parts of sulfonated oak powder, 6 parts of composite porous carbon, 6 parts of cage-type material, 1.2 parts of composite material, 0.3 parts of short fiber, 2 parts of conductive carbon black, 12 parts of sulfuric acid solution with a mass percentage concentration of 50%, 14 parts of deionized water, and 90 parts of lead powder;

[0043] The composite porous carbon preparation method is as follows:

[0044] Step 1: adding bismuth nitrate and cobalt nitrate into an ethanol aqueous solution to form a 100 ml metal solution, wherein the ethanol aqueous solution is an ethanol aqueous solution with a mass fraction of 50%, the concentration of bismuth ions in the metal solution is 50 mmol / L, and the concentration of cobalt ions in the metal solution is 50 mmol / L;

[0045] Step 2: Add the metal solution in step 1 to the reaction kettle, then add 10 mmol of 3,5-dicarboxyphenylboronic acid and 10 mmol of terephthalic acid, react at 150° C. for 24 hours, wash the product with ethanol three times, and dry it at 60° C. in vacuum to obtain a crystalline product;

[0046] Step 3: calcine the crystalline product in step 2 at 600°C for 9 hours in a nitrogen atmosphere to obtain composite porous carbon.

[0047] The cage material is prepared by molecular self-assembly of tetrapyridylporphyrin cobalt, cis-Pt(PEt3)2(OTf)2 and [1,1'-biphenyl]-3,3',5,5'-tetracarboxylate sodium, and the specific preparation method is as follows:

[0048] Step 1: Add 0.1 mol of tetrapyridylporphyrin cobalt and 0.4 mol of cis-Pt(PEt3)2(OTf)2 into 400 ml of acetone and heat to 50 °C for 12 h;

[0049] Step 2: Dissolve 0.1 mol of sodium [1,1'-biphenyl]-3,3',5,5'-tetracarboxylate in 100 ml of deionized water, add to the mixture in step 1, and heat to 50°C for 12 hours;

[0050] Step 3: Cool to room temperature, remove the solvent under nitrogen protection, and disperse the product in 100 ml of acetone. After dialyzing, add 300 ml of ether to produce precipitation, filter and dry to obtain a cage-type material.

[0051] The composite material is prepared by mixing and grinding sodium lignin sulfonate, lignin and barium sulfate in a weight ratio of 3:2:3.

[0052] The short fibers are acrylic fibers and have a length of 3 mm.

[0053] A preparation process of an anti-oxidation negative plate lead paste, characterized in that it comprises the following steps:

[0054] (a) weighing the above raw materials according to the above weight fractions, mechanically premixing the composite material and the conductive carbon black, adding the sulfonated oak powder, the composite porous carbon, the cage material and the short fiber after the premixing is uniform, and then mechanically mixing them, and after the premixing is uniform, dispersing the whole in the lead powder and dry stirring to obtain a mixture;

[0055] (b) adding deionized water to the mixture of step 1 and stirring evenly, then slowly adding sulfuric acid solution, controlling the system temperature at 50° C. during the acid addition process, and continuously stirring for 25 minutes throughout the process to prepare the antioxidant negative electrode lead paste.

[0056] An anti-oxidation negative electrode plate, the anti-oxidation negative electrode plate lead paste obtained by the above-mentioned preparation process is made by the following steps:

[0057] The anti-oxidation negative plate lead paste is applied to the negative grid plate and dried and cured; during drying and curing, the curing time is 30 hours, the temperature is 50° C., and the relative humidity is 95%; the drying time is 32 hours, and the temperature is 55° C.

[0058] Example 3

[0059] An antioxidant negative plate lead paste, comprising the following components in parts by weight: 2 parts of sulfonated oak powder, 10 parts of composite porous carbon, 7 parts of cage-type material, 2 parts of composite material, 0.5 parts of short fiber, 3 parts of conductive carbon black, 15 parts of sulfuric acid solution with a mass percentage concentration of 50%, 18 parts of deionized water, and 100 parts of lead powder;

[0060] The composite porous carbon preparation method is as follows:

[0061] Step 1: adding bismuth nitrate and cobalt nitrate into an ethanol aqueous solution to form a 100 ml metal solution, wherein the ethanol aqueous solution is an ethanol aqueous solution with a mass fraction of 50%, the concentration of bismuth ions in the metal solution is 50 mmol / L, and the concentration of cobalt ions in the metal solution is 50 mmol / L;

[0062] Step 2: Add the metal solution in step 1 to the reaction kettle, then add 10 mmol of 3,5-dicarboxyphenylboronic acid and 10 mmol of terephthalic acid, react at 200° C. for 24 hours, wash the product with ethanol three times, and dry it at 70° C. in vacuum to obtain a crystalline product;

[0063] Step 3: calcine the crystalline product in step 2 at 600°C for 9 hours in a nitrogen atmosphere to obtain composite porous carbon.

[0064] The cage material is prepared by molecular self-assembly of tetrapyridylporphyrin cobalt, cis-Pt(PEt3)2(OTf)2 and [1,1'-biphenyl]-3,3',5,5'-tetracarboxylate sodium, and the specific preparation method is as follows:

[0065] Step 1: Add 0.1 mol of tetrapyridylporphyrin cobalt and 0.4 mol of cis-Pt(PEt3)2(OTf)2 into 400 ml of acetone and heat to 50 °C for 12 h;

[0066] Step 2: Dissolve 0.1 mol of sodium [1,1'-biphenyl]-3,3',5,5'-tetracarboxylate in 100 ml of deionized water, add to the mixture in step 1, and heat to 50°C for 12 hours;

[0067] Step 3: Cool to room temperature, remove the solvent under nitrogen protection, and disperse the product in 100 ml of acetone. After dialyzing, add 300 ml of ether to produce a precipitate, filter and dry to obtain a cage-type material.

[0068] The composite material is prepared by mixing and grinding sodium lignin sulfonate, lignin and barium sulfate in a weight ratio of 3:2:3.

[0069] The short fibers are polyester and have a length of 4 mm.

[0070] A preparation process of an anti-oxidation negative plate lead paste, characterized in that it comprises the following steps:

[0071] (a) weighing the above raw materials according to the above weight fractions, mechanically premixing the composite material and the conductive carbon black, adding the sulfonated oak powder, the composite porous carbon, the cage material and the short fiber after the premixing is uniform, and then mechanically mixing them, and after the premixing is uniform, dispersing the whole in the lead powder and dry stirring to obtain a mixture;

[0072] (b) adding deionized water to the mixture of step 1 and stirring evenly, then slowly adding sulfuric acid solution, controlling the system temperature at 65° C. during the acid addition process, and continuously stirring for 30 minutes throughout the process to prepare the antioxidant negative electrode lead paste.

[0073] An anti-oxidation negative electrode plate, the anti-oxidation negative electrode plate lead paste obtained by the above-mentioned preparation process is made by the following steps:

[0074] The anti-oxidation negative plate lead paste is applied to the negative grid plate and dried and cured; during drying and curing, the curing time is 30 hours, the temperature is 50° C., and the relative humidity is 95%; the drying time is 32 hours, and the temperature is 55° C.

[0075] Comparative Example 1

[0076] An anti-oxidation negative plate lead paste, comprising the following components in parts by weight: 1.2 parts of sulfonated oak powder, 6 parts of cage-type materials, 1.2 parts of composite materials, 0.3 parts of short fibers, 2 parts of conductive carbon black, 12 parts of sulfuric acid solution with a mass percentage concentration of 50%, 14 parts of deionized water, and 90 parts of lead powder;

[0077] The cage material is prepared by molecular self-assembly of tetrapyridylporphyrin cobalt, cis-Pt(PEt3)2(OTf)2 and [1,1'-biphenyl]-3,3',5,5'-tetracarboxylate sodium, and the specific preparation method is as follows:

[0078] Step 1: Add 0.1 mol of tetrapyridylporphyrin cobalt and 0.4 mol of cis-Pt(PEt3)2(OTf)2 into 400 ml of acetone and heat to 50 °C for 12 h;

[0079] Step 2: Dissolve 0.1 mol of sodium [1,1'-biphenyl]-3,3',5,5'-tetracarboxylate in 100 ml of deionized water, add to the mixture in step 1, and heat to 50°C for 12 hours;

[0080] Step 3: Cool to room temperature, remove the solvent under nitrogen protection, and disperse the product in 100 ml of acetone. After dialyzing, add 300 ml of ether to produce precipitation, filter and dry to obtain a cage-type material.

[0081] The composite material is prepared by mixing and grinding sodium lignin sulfonate, lignin and barium sulfate in a weight ratio of 3:2:3.

[0082] The short fibers are acrylic fibers and have a length of 3 mm.

[0083] A preparation process of an anti-oxidation negative plate lead paste, characterized in that it comprises the following steps:

[0084] (a) weighing the above raw materials according to the above weight fractions, mechanically premixing the composite material and the conductive carbon black, adding the sulfonated oak powder, the cage material and the short fiber after the premixing is uniform, and then mechanically mixing them, and then dispersing the whole in the lead powder after the premixing is uniform, and dry stirring is performed to obtain a mixture;

[0085] (b) adding deionized water to the mixture of step 1 and stirring evenly, then slowly adding sulfuric acid solution, controlling the system temperature at 50° C. during the acid addition process, and continuously stirring for 25 minutes throughout the process to prepare the antioxidant negative electrode lead paste.

[0086] An anti-oxidation negative electrode plate, the anti-oxidation negative electrode plate lead paste obtained by the above-mentioned preparation process is made by the following steps:

[0087] The anti-oxidation negative plate lead paste is applied to the negative grid plate and dried and cured; during drying and curing, the curing time is 30 hours, the temperature is 50° C., and the relative humidity is 95%; the drying time is 32 hours, and the temperature is 55° C.

[0088] Comparative Example 2

[0089] An anti-oxidation negative plate lead paste, comprising the following components in parts by weight: 1.2 parts of sulfonated oak powder, 6 parts of composite porous carbon, 6 parts of cage-type material, 1.2 parts of composite material, 0.3 parts of short fiber, 2 parts of conductive carbon black, 12 parts of sulfuric acid solution with a mass percentage concentration of 50%, 14 parts of deionized water, and 90 parts of lead powder;

[0090] The composite porous carbon preparation method is as follows:

[0091] Step 1: adding bismuth nitrate to an ethanol aqueous solution to form a 100 ml metal solution, wherein the ethanol aqueous solution is an ethanol aqueous solution with a mass fraction of 50%, and the concentration of bismuth ions in the metal solution is 100 mmol / L;

[0092] Step 2: Add the metal solution in step 1 to the reaction kettle, then add 10 mmol of 3,5-dicarboxyphenylboronic acid and 10 mmol of terephthalic acid, react at 150° C. for 24 hours, wash the product with ethanol three times, and dry it at 60° C. in vacuum to obtain a crystalline product;

[0093] Step 3: calcine the crystalline product in step 2 at 600°C for 9 hours in a nitrogen atmosphere to obtain composite porous carbon.

[0094] The cage material is prepared by molecular self-assembly of tetrapyridylporphyrin cobalt, cis-Pt(PEt3)2(OTf)2 and [1,1'-biphenyl]-3,3',5,5'-tetracarboxylate sodium, and the specific preparation method is as follows:

[0095] Step 1: Add 0.1 mol of tetrapyridylporphyrin cobalt and 0.4 mol of cis-Pt(PEt3)2(OTf)2 into 400 ml of acetone and heat to 50 °C for 12 h;

[0096] Step 2: Dissolve 0.1 mol of sodium [1,1'-biphenyl]-3,3',5,5'-tetracarboxylate in 100 ml of deionized water, add to the mixture in step 1, and heat to 50°C for 12 hours;

[0097] Step 3: Cool to room temperature, remove the solvent under nitrogen protection, and disperse the product in 100 ml of acetone. After dialyzing, add 300 ml of ether to produce precipitation, filter and dry to obtain a cage-type material.

[0098] The composite material is prepared by mixing and grinding sodium lignin sulfonate, lignin and barium sulfate in a weight ratio of 3:2:3.

[0099] The short fibers are acrylic fibers and have a length of 3 mm.

[0100] A preparation process of an anti-oxidation negative plate lead paste, characterized in that it comprises the following steps:

[0101] (a) weighing the above raw materials according to the above weight fractions, mechanically premixing the composite material and the conductive carbon black, adding the sulfonated oak powder, the composite porous carbon, the cage material and the short fiber after the premixing is uniform, and then mechanically mixing them, and after the premixing is uniform, dispersing the whole in the lead powder and dry stirring to obtain a mixture;

[0102] (b) adding deionized water to the mixture of step 1 and stirring evenly, then slowly adding sulfuric acid solution, controlling the system temperature at 50° C. during the acid addition process, and continuously stirring for 25 minutes throughout the process to prepare the antioxidant negative electrode lead paste.

[0103] An anti-oxidation negative electrode plate, the anti-oxidation negative electrode plate lead paste obtained by the above-mentioned preparation process is made by the following steps:

[0104] The anti-oxidation negative plate lead paste is applied to the negative grid plate and dried and cured; during drying and curing, the curing time is 30 hours, the temperature is 50° C., and the relative humidity is 95%; the drying time is 32 hours, and the temperature is 55° C.

[0105] Comparative Example 3

[0106] An anti-oxidation negative plate lead paste, comprising the following components in parts by weight: 1.2 parts of sulfonated oak powder, 6 parts of composite porous carbon, 6 parts of cage-type material, 1.2 parts of composite material, 0.3 parts of short fiber, 2 parts of conductive carbon black, 12 parts of sulfuric acid solution with a mass percentage concentration of 50%, 14 parts of deionized water, and 90 parts of lead powder;

[0107] The composite porous carbon preparation method is as follows:

[0108] Step 1: adding cobalt nitrate to an ethanol aqueous solution to form a 100 ml metal solution, wherein the ethanol aqueous solution is an ethanol aqueous solution with a mass fraction of 50%, and the concentration of cobalt ions in the metal solution is 100 mmol / L;

[0109] Step 2: Add the metal solution in step 1 to the reaction kettle, then add 10 mmol of 3,5-dicarboxyphenylboronic acid and 10 mmol of terephthalic acid, react at 150° C. for 24 hours, wash the product with ethanol three times, and dry it at 60° C. in vacuum to obtain a crystalline product;

[0110] Step 3: calcine the crystalline product in step 2 at 600°C for 9 hours in a nitrogen atmosphere to obtain composite porous carbon.

[0111] The cage material is prepared by molecular self-assembly of tetrapyridylporphyrin cobalt, cis-Pt(PEt3)2(OTf)2 and [1,1'-biphenyl]-3,3',5,5'-tetracarboxylate sodium, and the specific preparation method is as follows:

[0112] Step 1: Add 0.1 mol of tetrapyridylporphyrin cobalt and 0.4 mol of cis-Pt(PEt3)2(OTf)2 into 400 ml of acetone and heat to 50 °C for 12 h;

[0113] Step 2: Dissolve 0.1 mol of sodium [1,1'-biphenyl]-3,3',5,5'-tetracarboxylate in 100 ml of deionized water, add to the mixture in step 1, and heat to 50°C for 12 hours;

[0114] Step 3: Cool to room temperature, remove the solvent under nitrogen protection, and disperse the product in 100 ml of acetone. After dialyzing, add 300 ml of ether to produce precipitation, filter and dry to obtain a cage-type material.

[0115] The composite material is prepared by mixing and grinding sodium lignin sulfonate, lignin and barium sulfate in a weight ratio of 3:2:3.

[0116] The short fibers are acrylic fibers and have a length of 3 mm.

[0117] A preparation process of an anti-oxidation negative plate lead paste, characterized in that it comprises the following steps:

[0118] (a) weighing the above raw materials according to the above weight fractions, mechanically premixing the composite material and the conductive carbon black, adding the sulfonated oak powder, the composite porous carbon, the cage material and the short fiber after the premixing is uniform, and then mechanically mixing them, and after the premixing is uniform, dispersing the whole in the lead powder and dry stirring to obtain a mixture;

[0119] (b) adding deionized water to the mixture of step 1 and stirring evenly, then slowly adding sulfuric acid solution, controlling the system temperature at 50° C. during the acid addition process, and continuously stirring for 25 minutes throughout the process to prepare the antioxidant negative electrode lead paste.

[0120] An anti-oxidation negative electrode plate, the anti-oxidation negative electrode plate lead paste obtained by the above-mentioned preparation process is made by the following steps:

[0121] The anti-oxidation negative plate lead paste is applied to the negative grid plate and dried and cured; during drying and curing, the curing time is 30 hours, the temperature is 50° C., and the relative humidity is 95%; the drying time is 32 hours, and the temperature is 55° C.

[0122] Comparative Example 4

[0123] An anti-oxidation negative plate lead paste, comprising the following components in parts by weight: 1.2 parts of sulfonated oak powder, 6 parts of composite porous carbon, 6 parts of cage-type material, 1.2 parts of composite material, 0.3 parts of short fiber, 2 parts of conductive carbon black, 12 parts of sulfuric acid solution with a mass percentage concentration of 50%, 14 parts of deionized water, and 90 parts of lead powder;

[0124] The composite porous carbon preparation method is as follows:

[0125] Step 1: adding bismuth nitrate and cobalt nitrate into an ethanol aqueous solution to form a 100 ml metal solution, wherein the ethanol aqueous solution is an ethanol aqueous solution with a mass fraction of 50%, the concentration of bismuth ions in the metal solution is 50 mmol / L, and the concentration of cobalt ions in the metal solution is 50 mmol / L;

[0126] Step 2: Add the metal solution in step 1 to the reaction kettle, then add 10 mmol of 3,5-dicarboxybenzoic acid and 10 mmol of terephthalic acid, react at 150° C. for 24 hours, wash the product with ethanol three times, and dry it at 60° C. in vacuum to obtain a crystalline product;

[0127] Step 3: calcine the crystalline product in step 2 at 600°C for 9 hours in a nitrogen atmosphere to obtain composite porous carbon.

[0128] The cage material is prepared by molecular self-assembly of tetrapyridylporphyrin cobalt, cis-Pt(PEt3)2(OTf)2 and [1,1'-biphenyl]-3,3',5,5'-tetracarboxylate sodium, and the specific preparation method is as follows:

[0129] Step 1: Add 0.1 mol of tetrapyridylporphyrin cobalt and 0.4 mol of cis-Pt(PEt3)2(OTf)2 into 400 ml of acetone and heat to 50 °C for 12 h;

[0130] Step 2: Dissolve 0.1 mol of sodium [1,1'-biphenyl]-3,3',5,5'-tetracarboxylate in 100 ml of deionized water, add to the mixture in step 1, and heat to 50°C for 12 hours;

[0131] Step 3: Cool to room temperature, remove the solvent under nitrogen protection, and disperse the product in 100 ml of acetone. After dialyzing, add 300 ml of ether to produce precipitation, filter and dry to obtain a cage-type material.

[0132] The composite material is prepared by mixing and grinding sodium lignin sulfonate, lignin and barium sulfate in a weight ratio of 3:2:3.

[0133] The short fibers are acrylic fibers and have a length of 3 mm.

[0134] A preparation process of an anti-oxidation negative plate lead paste, characterized in that it comprises the following steps:

[0135] (a) weighing the above raw materials according to the above weight fractions, mechanically premixing the composite material and the conductive carbon black, adding the sulfonated oak powder, the composite porous carbon, the cage material and the short fiber after the premixing is uniform, and then mechanically mixing them, and after the premixing is uniform, dispersing the whole in the lead powder and dry stirring to obtain a mixture;

[0136] (b) adding deionized water to the mixture of step 1 and stirring evenly, then slowly adding sulfuric acid solution, controlling the system temperature at 50° C. during the acid addition process, and continuously stirring for 25 minutes throughout the process to prepare the antioxidant negative electrode lead paste.

[0137] An anti-oxidation negative electrode plate, the anti-oxidation negative electrode plate lead paste obtained by the above-mentioned preparation process is made by the following steps:

[0138] The anti-oxidation negative plate lead paste is applied to the negative grid plate and dried and cured; during drying and curing, the curing time is 30 hours, the temperature is 50° C., and the relative humidity is 95%; the drying time is 32 hours, and the temperature is 55° C.

[0139] Comparative Example 5

[0140] An anti-oxidation negative plate lead paste, comprising the following components in parts by weight: 1.2 parts of sulfonated oak powder, 6 parts of composite porous carbon, 1.2 parts of composite material, 0.3 parts of short fiber, 2 parts of conductive carbon black, 12 parts of sulfuric acid solution with a mass percentage concentration of 50%, 14 parts of deionized water, and 90 parts of lead powder;

[0141] The composite porous carbon preparation method is as follows:

[0142] Step 1: adding bismuth nitrate and cobalt nitrate into an ethanol aqueous solution to form a 100 ml metal solution, wherein the ethanol aqueous solution is an ethanol aqueous solution with a mass fraction of 50%, the concentration of bismuth ions in the metal solution is 50 mmol / L, and the concentration of cobalt ions in the metal solution is 50 mmol / L;

[0143] Step 2: Add the metal solution in step 1 to the reaction kettle, then add 10 mmol of 3,5-dicarboxybenzoic acid and 10 mmol of terephthalic acid, react at 150° C. for 24 hours, wash the product with ethanol three times, and dry it at 60° C. in vacuum to obtain a crystalline product;

[0144] Step 3: calcine the crystalline product in step 2 at 600°C for 9 hours in a nitrogen atmosphere to obtain composite porous carbon.

[0145] The composite material is prepared by mixing and grinding sodium lignin sulfonate, lignin and barium sulfate in a weight ratio of 3:2:3.

[0146] The short fibers are acrylic fibers and have a length of 3 mm.

[0147] A preparation process of an anti-oxidation negative plate lead paste, characterized in that it comprises the following steps:

[0148] (a) weighing the above raw materials according to the above weight fractions, mechanically premixing the composite material and the conductive carbon black, adding the sulfonated oak powder, the composite porous carbon and the short fibers after the premixing is uniform, and then mechanically mixing them, and then dispersing the whole in the lead powder after the premixing is uniform, and dry stirring is performed to obtain a mixture;

[0149] (b) adding deionized water to the mixture of step 1 and stirring evenly, then slowly adding sulfuric acid solution, controlling the system temperature at 50° C. during the acid addition process, and continuously stirring for 25 minutes throughout the process to prepare the antioxidant negative electrode lead paste.

[0150] An anti-oxidation negative electrode plate, the anti-oxidation negative electrode plate lead paste obtained by the above-mentioned preparation process is made by the following steps:

[0151] The anti-oxidation negative plate lead paste is applied to the negative grid plate and dried and cured; during drying and curing, the curing time is 30 hours, the temperature is 50° C., and the relative humidity is 95%; the drying time is 32 hours, and the temperature is 55° C.

[0152] The antioxidant negative electrode plates prepared in the above examples and comparative examples were made into lead-acid battery grids and then into lead-acid batteries, and the following performance test experiments were carried out:

[0153] 1. Cycle life test

[0154] Cycle life test method: In a 25℃ environment, charge for 16h at a constant voltage of 14.1V and a current limit of 75A, and then discharge at a constant current of 50A to a termination voltage of 11.0V for one cycle. When the discharge capacity of the entire battery group is less than 80% of the rated capacity, the life ends.

[0155] 2. Capacity test

[0156] The test was conducted according to the standard GB / T22199-2008.

[0157] Table 1. Test results of samples of various embodiments

[0158]

[0159] Note: The capacity decay rate in the table is the decay value after 50 cycles.

[0160] As shown in Table 1, the lead-acid battery made of the antioxidant negative plate lead paste of the present invention has a longer cycle life and a significantly reduced capacity decay rate, indicating that the addition of the composite porous carbon increases the specific surface area of ​​the plate, improves the wettability between the electrolyte and the electrode material, and the doping of the boron element significantly improves the performance of the plate, thereby increasing the battery life and slowing down the decay. The addition of the cage material inhibits the continuous growth of lead sulfate crystals, making it easier to reduce to lead dioxide, and reduces the loss of water in the electrode liquid, thereby increasing the battery life and decay rate.

Claims

1. An anti-oxidation negative plate lead paste, characterized in that: The invention comprises the following components in parts by weight: 0.5-2 parts of sulfonated oak powder, 3-10 parts of composite porous carbon, 5-7 parts of cage-type material, 0.5-2 parts of composite material, 0.1-0.5 parts of short fiber, 1-3 parts of conductive carbon black, 8-15 parts of sulfuric acid solution with a mass percentage concentration of 50%, 9-18 parts of deionized water, and 80-100 parts of lead powder; The composite porous carbon preparation method is as follows: Step 1: adding bismuth nitrate and cobalt nitrate into an ethanol aqueous solution to form a 100 ml metal solution, wherein the ethanol aqueous solution is an ethanol aqueous solution with a mass fraction of 50%, the concentration of bismuth ions in the metal solution is 50 mmol / L, and the concentration of cobalt ions in the metal solution is 50 mmol / L; Step 2: Add the metal solution in step 1 to the reaction kettle, then add 10 mmol of 3,5-dicarboxyphenylboronic acid and 10 mmol of terephthalic acid, react at 100-200° C. for 24 hours, wash the product with ethanol three times, and dry it at 50-70° C. in vacuum to obtain a crystalline product; Step 3: calcining the crystalline product in step 2 at 600° C. for 9 h in a nitrogen atmosphere to obtain a composite porous carbon; The cage material is formed by molecular self-assembly of tetrapyridylporphyrin cobalt, cis-Pt(PEt3)2(OTf)2 and [1,1'-biphenyl]-3,3',5,5'-tetracarboxylate sodium; The method for preparing the cage material is as follows: Step 1: Add 0.1 mol of tetrapyridylporphyrin cobalt and 0.4 mol of cis-Pt(PEt3)2(OTf)2 into 400 ml of acetone and heat to 50 °C for 12 h; Step 2: Dissolve 0.1 mol of sodium [1,1'-biphenyl]-3,3',5,5'-tetracarboxylate in 100 ml of deionized water, add to the mixture in step 1, and heat to 50°C for 12 hours; Step 3: Cool to room temperature, remove the solvent under nitrogen protection, and disperse the product in 100 ml of acetone. After dialyzing, add 300 ml of ether to produce a precipitate, filter and dry to obtain a cage-type material.

2. The anti-oxidation negative plate lead paste according to claim 1, characterized in that: The composite material is prepared by mixing and grinding sodium lignin sulfonate, lignin and barium sulfate in a weight ratio of 3:2:

3.

3. The anti-oxidation negative electrode plate lead paste according to claim 1, characterized in that: The short fiber is one of nylon, acrylic fiber and polyester, and has a length of 2-4 mm.

4. A process for preparing an anti-oxidation negative plate lead paste as claimed in claim 1, characterized in that: The following steps are involved: (a) weighing the above raw materials according to the above weight fractions, mechanically premixing the composite material and the conductive carbon black, adding the sulfonated oak powder, the composite porous carbon, the cage material and the short fiber after the premixing is uniform, and then mechanically mixing them, and after the premixing is uniform, dispersing the whole in the lead powder and dry stirring to obtain a mixture; (b) adding deionized water to the mixture of step 1 and stirring evenly, then slowly adding sulfuric acid solution, controlling the system temperature between 30-65° C. during the acid addition process, and continuously stirring for 20-30 minutes throughout the process to prepare the antioxidant negative electrode lead paste.

5. The antioxidant negative electrode plate according to claim 1, wherein the antioxidant negative electrode plate lead paste is obtained by the preparation process according to claim 4, characterized in that: The method is made by the following steps: applying the anti-oxidation negative plate lead paste to the negative grid plate and drying and curing the negative plate; during drying and curing, the curing time is 30 hours, the temperature is 50° C., and the relative humidity is 95%; the drying time is 32 hours and the temperature is 55° C.

Citation Information

Patent Citations

  • Lead-acid storage battery electrolyte and preparation method thereof

    CN112072187A

  • Lead acid accumulator battery

    UA76026C2